2004
DOI: 10.1007/s10227-004-0806-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel Opportunities in the Treatment and Prevention of Scarring

Abstract: Numerous treatments have been described for the treatment and prevention of scars, but the optimal management strategy is yet to be defined. In this article we present and evaluate new opportunities for the treatment and prevention of hypertrophic scars, keloids, and atrophic scars. Clinical, animal, and in vitro studies reporting novel techniques for the treatment and prevention of scarring were identified primarily from the MEDLINE/PubMed database. We found that a variety of new treatments exist with potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…15 Despite numerous hypotheses about keloid formation that have been investigated, its exact mechanism still has not been determined. Furthermore, a broad range of available treatment modalities have been used for keloid, including surgical excision, laser therapy, silicone therapy, intralesional corticosteroids, 5-fluorouracil and imiquimod, [16][17][18][19][20][21][22] but none are consistently effective in flattening existing keloid, relieving associated symptoms and reducing recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…15 Despite numerous hypotheses about keloid formation that have been investigated, its exact mechanism still has not been determined. Furthermore, a broad range of available treatment modalities have been used for keloid, including surgical excision, laser therapy, silicone therapy, intralesional corticosteroids, 5-fluorouracil and imiquimod, [16][17][18][19][20][21][22] but none are consistently effective in flattening existing keloid, relieving associated symptoms and reducing recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…71 On an experimental level, IFN has clearly shown potential efficacy as an antifibrotic agent which can potentially decrease the overproduction of collagen and glycosaminoglycans and simultaneously normalize the low level of collagenase activity observed in keloidal tissue. 53 Findings from clinical trials reveal conflicting data, however, for the efficacy of IFN on keloid treatment. Further clinical investigation, in terms of controlled, randomized trials, should take place to enrich the existing data and illuminate the prospective of IFN as a potent therapeutic agent in the treatment of keloids and HTS.…”
Section: Interferonmentioning
confidence: 97%
“…They are widely used in a variety of clinical scenarios such as condylomata accuminata, basal 52 IFNs decrease the overproduction of collagen and glycosaminoglycans by scar-forming fibroblasts and increase the level of collagenase activity. 53 Studies have shown that IFN-g promotes myofibroblast apoptosis and inhibits its differentiation, while IFN-a inhibits wound contraction in vitro. 54,55 The use of IFN has been associated with mild side effects such as flu-like symptoms.…”
Section: Interferonmentioning
confidence: 99%
“…Different options such as intralesional injections of bleomycin or corticosteroids either alone or combined with cryotherapy, compression therapy, silicone sheeting, radiation therapy, laser therapy, 5-fluorouracil, interferon, retinoids, imiquimod 5% cream, tacrolimus, verapamil and botulin toxin have been used, most of them with the aim of achieving the best functional and cosmetic solution possible. 1-5 …”
Section: Introductionmentioning
confidence: 99%